Performance of pre-cracked RC beams shear strengthened with NSM CFRP laminates - Dias, Salvador J. E. (2012)
The strengthening of an existing Reinforced Concrete (RC) structure often involves concrete in a cracked state. To evaluate the effect of existing cracks on the behavior of RC beams shear strengthened according to the Near Surface Mounted (NSM) technique with Carbon Fiber Reinforced Polymer (CFRP) laminates, an experimental program was carried. NSM CFRP laminates were applied in RC beams with or without cracks prior the application of the shear strengthening intervention. The main results of this experimental research are presented and analyzed in terms of the structural behavior of the beams, failure modes and effectiveness of the NSM technique with CFRP laminates. The principal difference of the behavior of NSM CFRP beams with and without pre-cracks can be resumed to an expected loss of initial stiffness in the pre-cracked specimens. However, the pre-cracking did not affect the efficacy of the NSM shear strengthening technique in terms of load carrying capacity and ultimate deflection.